EFEKTIVITAS MUSIK KLASIK DALAM MENGURANGI KECEMASAN MATEMATIKA MURID - Deny Hadi Siswanto; Kintoko Kintoko; Tarso Tarso (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Mathematics is often considered a difficult subject and a source of anxiety for many students, a phenomenon known as math anxiety. This anxiety negatively affects students' conceptual understanding, learning motivation, and academic performance. One strategy that can be implemented to reduce math anxiety is the use of classical music. Classical music is known to have a relaxing effect that can reduce stress, enhance focus, and create a more comfortable and conducive learning environment. This study aims to examine the effectiveness of classical music in reducing math anxiety among 11th-grade students at Muhammadiyah Mlati senior high school (28 students) through an experimental approach. The research employs a quasi-experimental design using a pretest-posttest control group method, where students' anxiety levels are measured before and after the intervention with classical music. The findings of this study are expected to provide new insights into the role of music in improving the quality of mathematics learning and serve as a foundation for developing more innovative and holistic teaching strategies. Integrating classical music into mathematics instruction is not only an innovation but also a strategic step in creating a more supportive and enjoyable learning environment. This approach allows students to learn with greater confidence, better understand mathematical concepts, and achieve optimal learning outcomes